The Use of Digital Marketing in the Efficiency and Transparency of Managing Da'wah Funds at Masjid Akbar Surabaya - Ruba'i Ruba'i; Novie Andrie Zakariya (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2025)
This study aims to examine the utilization of digital marketing in improving efficiency and transparency in the management of da’wah funds at Masjid Akbar Surabaya. The research employed a qualitative case study approach by collecting data through in-depth interviews with mosque administrators, active donors, and congregants, as well as direct observation and document analysis of digital financial reports. The results indicate that the application of digital marketing—through social media, websites, QR code payments, and online donation platforms—has significantly enhanced operational efficiency by reducing processing time, administrative costs, and human errors. Furthermore, transparency has increased through the publication of monthly financial reports and automatic digital receipts accessible to donors. This improvement has strengthened public trust and encouraged greater participation in supporting da’wah programs. However, the study also identifies challenges related to digital literacy and data security awareness among congregants. The findings contribute to the development of digital religious management and provide practical insights for Islamic institutions seeking to establish efficient and transparent financial governance through digital transformation. Keywords: Digital marketing; Efficiency; Transparency; Da’wah funds; Islamic management.